Successful Medical Therapy for Hypophosphatemic Rickets due to Mitochondrial Complex I Deficiency Induced de Toni-Debré-Fanconi Syndrome. (10th December 2013) - Bowden, Sasigarn A.; Patel, Hiren P.; Beebe, Allan; McBride, Kim L.
Abstract : Primary de Toni-Debré-Fanconi syndrome is a non-FGF23-mediated hypophosphatemic disorder due to a primary defect in renal proximal tubule cell function resulting in hyperphosphaturia, renal tubular acidosis, glycosuria, and generalized aminoaciduria. The orthopaedic sequela and response to treatment of this rare disorder are limited in the literature. Herein we report a long term followup of a 10-year-old female presenting at 1 year of age with rickets initially misdiagnosed as vitamin D deficiency rickets. She was referred to the metabolic bone and genetics clinics at 5 years of age with severe genu valgum deformities of 24 degrees and worsening rickets. She had polyuria, polydipsia, enuresis, and bone pain. Diagnosis of hypophosphatemic rickets due to de Toni-Debré-Fanconi syndrome was subsequently made. Respiratory chain enzyme analysis identified a complex I mitochondrial deficiency as the underlying cause. She was treated with phosphate (50–70 mg/kg/day), calcitriol (30 ng/kg/day), and sodium citrate with resolution of bone pain and normal growth. By 10 years of age, her genu valgus deformities were 4 degrees with healing of rickets. Her excellent orthopaedic outcome despite late proper medical therapy is likely due to the intrinsic renal tubular defect that is more responsive to combined alkali, phosphate, and calcitriol therapy.